The complete mitochondrial genome of a forensic potential wasp, Vespa auraria (Smith) - ZiChao Liu; HongMei Tang; Lei Tong; Xingzhu Liu; FanMing Meng (Mitochondrial DNA. Part B. Resources, 2020)
Vespa auraria (Smith) is a common wasp species which is broadly distributed in south Asia. This species was spotted in filed forensic studies and disrupted the insect succession on the decaying corpse. Complete mitochondrial genome of V. auraria was presented here for its forensically potential influence. The mitogenome was assemblied to 18613 bp in length. The nucleotide composition of present mitogenome was calculated (A: 40.1%, G: 5.5%, T: 41.7%, C: 12.7%). Gene annotation analysis found 22 tRNA, 2 rRNA, and 13 protein-coding genes (PCGs). All the tRNA sequences could be folded into the typical structure of clover-leaf with the excepstion of tRNA-Ser (AGN). Phylogenetic development was analyzed based on V. auraria with other species of Hymenoptera.